Behavior of Chinese enterprises in evaluating wind power projects: A review based on survey. (March 2015) - Wu, Zhongqun; Sun, Hongxia
Abstract: This study performed a comparative analysis of the different methods used for different projects based on a survey regarding the evaluation behavior of Chinese enterprises on wind power projects. According to the survey results, Chinese enterprises used mainly traditional methods – the income method and the market method – to evaluate wind power projects. Only a minority of the companies used the relatively new real options method. The newest strategic value method was not in use at all. The study tried to explain how enterprises assess the value of wind power projects and to summarize the general principles and factors considered in the evaluation process. The study identified some problems in the evaluation process and some suggestions for improving the methods used and for related policies. The study also opened another window for investors worldwide to understand how Chinese enterprises evaluate wind power projects.